Astragaloside IV regulates insulin resistance and inflammatory response of adipocytes via modulating miR-21/PTEN/PI3K/AKT signaling - Guo, Xuxi; Yin, Taoqing; Chen, Dongni; Xu, Shuai; Ye, Renqun; Zhang, Yue (Endocrine, metabolic & immune disorders drug targets, 2023)
Background The progression of Type 2 Diabetes Mellitus (T2DM) can lead to various complications. Compounds derived from natural products have been found to be effective in combatting T2DM. This study aimed to investigate the effects of Astragaloside IV (AS-IV) on insulin resistance and the inflammatory response of adipocytes. The study also aimed to determine the downstream signaling pathways involved. Materials and methods The glucose consumption of adipocytes was assessed using a glucose assay kit. qRT-PCR, Western blot, and ELISA assays were used to measure mRNA and protein levels. The interaction between miR-21 and PTEN was assessed using a Dual-luciferase reporter assay. Results The results showed that AS-IV increased glucose consumption and the expression of GLUT-4 in adipocytes with insulin resistance in a concentration-dependent manner. However, AS-IV decreased the protein levels of TNF-α and IL-6 in these cells. Additionally, AS-IV up-regulated miR-21 expression in adipocytes with insulin resistance in a concentration-dependent manner. Furthermore, miR-21 overexpression increased glucose consumption and GLUT-4 expression but decreased TNF-α and IL-6 protein levels in adipocytes. Conversely, miR-21 inhibition attenuated the AS-IV-induced increase in glucose consumption and GLUT-4 expression and the decrease in TNF-α and IL-6 protein levels in adipocytes. MiR-21 also inversely regulated PTEN in adipocytes, and PTEN overexpression had effects similar to miR-21 inhibition in AS-IV-treated adipocytes. Finally, AS-IV up-regulated p-PI3K and p-AKT protein expression in adipocytes, which was attenuated by miR-21 inhibition. Conclusion The study concluded that AS-IV attenuated insulin resistance and the inflammatory response in adipocytes. The mechanistic studies indicated that AS-IV modulated the miR-21/PTEN/PI3K/AKT signaling in adipocytes to exert these effects.